Estimation of regional surface deformation post the 2001 Bhuj earthquake in the Kachchh region, Western India using RADAR interferometry. Issue 18 (17th September 2022) - Kandregula, Raj Sunil; Kothyari, Girish Ch; Swamy, K. V.; Kumar Taloor, Ajay; Lakhote, Abhishek; Chauhan, Gaurav; Thakkar, M. G.; Pathak, Vamdev; Malik, Kapil
Abstract: The key objective of the present study is to estimate the surface displacement and to understand/monitor the active deformation pattern in the Kachchh region post the 2001 Bhuj Earthquake by implementing the Persistent Scatterer Interferometric Synthetic Aperture Radar (PSI) and Differential Interferometric Synthetic Aperture Radar (DInSAR) techniques. We employed the ENVISAT ASAR (15 images), ALOS PALSAR (6 pairs) and SENTINEL-1A (117 images) data sets acquired during the periods 2003–2005, 2007–2009, and 2016–2020 respectively. The PSI results of the Envisat dataset reveals that the Kachchh mainland region has undergone an average surface deformation of ± 22 mm/yr during 2003–2005. The maximum displacement observed from the ALOS PALSAR data sets (Window-1 to 6) during the period 2007–2009 is ∼ ± 1.2 cm. Further, the ground displacement observed from the Sentinel-1A dataset during the period 2016–2020 is ±16 mm/yr for the west-central region and 6 mm/yr uplift and 8 mm/yr subsidence in the eastern Kachchh mainland region. Surprisingly, high rate of deformation is detected towards the Pachham Island, Banni, Rann and the eastern region of the Kachchh after the 2001 Bhuj event. Correlating the results of different data sets, it is concluded that the deformation is high near the vicinity of the fault zones indicating the tectonically active nature of the faults. From the obtained results, we infer that, post the 2001 Bhuj earthquake, the surface displacement in the Kachchh mainland region is escalated till 2009 which is due to continuous aftershock activity and then started declining because of the ongoing seismic settlement. The acquired deformation rates are correlating well with the GPS derived displacement rates. Further, our results will assist in accurately demarcating the extent of the fault zones and also helps in precisely marking the areas undergoing active deformation, which will aid in micro zonation studies, mitigation planning and also for the preparation of an active tectonic map for the region.